2009
DOI: 10.1002/ange.200902929
|View full text |Cite
|
Sign up to set email alerts
|

Polyhedral Organic Microcrystals: From Cubes to Rhombic Dodecahedra

Abstract: Facettenreich: Die gezielte Synthese hochsymmetrischer niedermolekularer organischer Mikrokristalle mit Formen von Würfeln über angeschnittene Würfel zu rhombischen Dodekaedern (siehe Bild) gelang durch Änderungen in der Löslichkeit, die die Wachstumsgeschwindigkeit in 〈100〉‐Richtung relativ zu der in 〈110〉‐Richtung erheblich beeinflusst. Unterschiedliche Morphologien haben auch unterschiedliche optische Eigenschaften der Kristalle zur Folge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…5 mm in width) has a D 4h symmetry with four sails, in which the dihedral angles among the sails are almost 90 degrees. [21,22] The SEM image showed that the self-assembly of ACPC 7 produced the rodlike 3D structure R P (Figure 2 b), which is completely different from W W . Increasing the concentration of the heptamer solution resulted in larger assembled structures (e.g., a heptamer concentration of 4 mg mL À1 resulted in structures with widths of ca.…”
mentioning
confidence: 98%
“…5 mm in width) has a D 4h symmetry with four sails, in which the dihedral angles among the sails are almost 90 degrees. [21,22] The SEM image showed that the self-assembly of ACPC 7 produced the rodlike 3D structure R P (Figure 2 b), which is completely different from W W . Increasing the concentration of the heptamer solution resulted in larger assembled structures (e.g., a heptamer concentration of 4 mg mL À1 resulted in structures with widths of ca.…”
mentioning
confidence: 98%
“…For example, Zhang et al. found that 2,5,8,11‐tetra‐tert‐butylperylene (TBPe) molecules form both normal cubes and truncated cubes in a surfactant (P123) solution …”
Section: Non‐templated Synthesismentioning
confidence: 99%
“…This principle also applies to the assembly of foldectures. Several studies on surfactant‐assisted synthesis of organic crystals, including one of our recent studies, attributed 3D shape selection to the facet‐specific adhesion of surfactant molecules and anisotropic passivation effect ,. However, the inherent dynamic nature of surfactant molecules hinders a clear rationalization of 3D shape evolution and the corresponding assembly mechanisms .…”
Section: Introductionmentioning
confidence: 97%